Strategic implications of the employee performance management in emerging markets - Gregor, Richard; Sedláčková, Helena; Jiránková, Darina; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2008)
This thesis is dealing with the topic of the strategic performance management and cultural consequences of its implementation at emerging markets. The foremost goal of this thesis was to break down key issues which should be addressed by C-level management when considering implementation of Balanced Scorecards in emerging markets. Key issues which were addressed in this thesis: Cultural differences between emerging and developed countries; Knowledge worker as the key production factor in services; Theory of the Performance Management; Theory of Balanced Scorecards; Strategic implications of the implementation of Balanced Scorecards; Alternative approaches to Balanced Scorecards
Vedoucí práce: Helena Sedláčková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2008
Rok obhajoby 2008
Keywords: podniková ekonomika a management [obor dipl. práce]; management; diplomové práce; management; master's theses